Pengelolaan Esktrakurikuler Mewarnai Dan Kaligrafi Dalam Meningkatkan Prestasi Nonakademik Siswa MDTA Nurul Hidayah - Atika Zahro Aauliya; Masnipal (Jurnal Riset Pendidikan Agama Islam, 2025)
Abstract. This research is motivated by the importance of developing students' non-academic potential as a form of balance between academic and non-academic achievements. MDTA Nurul Hidayah has extracurricular programs in coloring and calligraphy to improve students' non-academic achievements. Based on this, the research questions are formulated as follows: (1) How is the planning and management of the coloring and calligraphy extracurricular program? (2) How is the implementation of the coloring and calligraphy extracurricular program? (3) How is the evaluation conducted in the management of the coloring and calligraphy extracurricular program? (4) What challenges are faced in managing the coloring and calligraphy extracurricular program?. This study uses a qualitative approach with a case study method. Data is collected through interviews, observations, and documentation. The data analysis technique used is descriptive analysis, consisting of data reduction, data presentation, and conclusion drawing. The results show that the program planning is well conducted through problem diagnosis, goal setting, and evaluation planning. The program is implemented as planned, supported by the head of MDTA, the curriculum coordinator, and the availability of facilities. Evaluation is carried out regularly once a month. Success factors of the program include parental support, enrichment books, student interest, and teacher attention. Challenges include limited equipment, long training duration, and difficulty in controlling students' moods. Abstrak. Penelitian ini dilatar belakangi oleh pentingnya pengembangan potensi nonakademik siswa sebagai bentuk keseimbangan antara prestasi akademik dan nonakademik. MDTA Nurul Hidayah memiliki program ekstrakurikuler mewarnai dan kaligrafi untuk meningkatkan prestasi nonakademik siswa. Berdasarkan fenomena tersebut, rumusan masalah dalam penelitian ini yaitu: (1) Bagaimana perencanaan pengelolaan program ekstrakurikuler mewarnai dan kaligrafi? (2) Bagaimana pelaksanaan program ekstrakurikuler mewarnai dan kaligrafi? (3) Bagaimana evaluasi yang dilakukan dalam pengelolaan program ekstrakurikuler mewarnai dan kaligrafi? (4) Apa saja kendala yang dihadapi dalam pengelolaan program ekstrakurikuler mewarnai dan kaligrafi?. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Teknik analisis data pada penelitian ini yakni analisis deskriptif dengan tahapan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini menunjukkan bahwa perencanaan program dilakukan dengan baik melalui diagnosis masalah, penetapan tujuan, dan perencanaan evaluasi. Pelaksanaan program berjalan sesuai rencana, yang didukung oleh kepala madrasah MDTA, koordinator kurikulum, dan tersedianya sarana prasarana. Evaluasi dilakukan secara rutin sebulan sekali. Faktor keberhasilan program meliputi dukungan orang tua, buku pengayaan dan minat siswa. Kendala yang dihadapi mencakup keterbatasan alat, durasi latihan yang panjang, dan kesulitan mengontrol mood siswa.